ANALISIS PENERAPAN PERJANJIAN INTERNASIONAL MEREK TERHADAP MEREK TERKENAL DI INDONESIA - Sabrina Aurellia; Christine S.T. Kansil (Fakultas Hukum Universitas Tarumanagara, 2020)
There are several viewpoints in determine a mark is a well-known trademark. Viewpoints gives confusion for the authorities in determining a well-known trademark. Well-known trademark as one of intellectual property rights has the right to be protected. Protection needs legal certainty. In order to provide legal certainty, the World Intellectual Property Organization initiates to establish international agreement, such as Paris Convention for the Protection of IndustriaI Property, The Agreement on Trade-ReIated Aspects of InteIIectual Property Rights 1995, and the Trademark Law Treaty. Indonesia as a member of the World Intellectual Property Organization ratifies the international agreements. The international agreement also became the basis of Indonesia’s intellectual property law, including well-known trademarks. The legal certainty in Indonesia for well-known marks can only be achieved with regulations and verdicts. Well-known mark is regulated in Act Number 20 Year 2016 and the Regulation of the Minister of Law and Human Rights Number 67 Year 2016. In fact, Indonesia’s regulations and verdict are not enough to hold off well-known mark cases. One of the cases is Sentence Number 04/Pdt. Sus.-Merek/2019/PN Niaga Jkt. Pst. AUTUMNPAPER LIMITED as the owner of the brand “ALEXANDER MCQUEEN” filed a lawsuit in 2019 to determine that “ALEXANDER MCQUEEN” is a well-known trademark in Indonesia. AUTUMNPAPER LIMITED also filed a lawsuit to cancel the registration of “MC QUEEN” in Indonesia based on Indonesia’s Act and Regulations.